THE INFLUENCE OF FINANCIAL INCLUSION ON THE PERFORMANCE OF MICRO SMALL AND MEDIUM ENTERPRISES IN NORTH SULAWESI - Lumenta, Ulrigh Z.; Worang, Frederik G. (Universitas Sam Ratulangi, 2019)
Bank and non-bank financial institutions have an important role in a country's financial system. One of them is maintaining financial stability in a country's economy. Economic growth and development in Indonesia automatically contribute to the development of financial institutions, both banks, and non-banks. The aims of this research is to analyze the influence of financial inclusion on the performance of micro small medium enterprises in north sulawesi. The type of this research is descriptive research and used qualitative research method. The population in this research is micro small medium enterprises in north sulawesi. the sample in this research is consisting of 20 informants. The founding of this research that the financial inclusion have a positive effect on the performance of micro small medium enterprises in north sulawesi. The result of this research that financial inclusion in North Sulawesi have a good effect for the increase of Profit, increase of Labor or employee, and increase of Production on the micro small medium enterprises. Recommendation for micro small medium enterprises, they can take advantage of easy access or accessibility to financial institutions. With the existence of financial inclusion, business people are increasingly becoming obsessed with accessing existing financial institutions. So that MSMEs can increase capital from financial institutions because of the ease of access to these financial institutions.Keywords: financial inclusion, micro small medium enterprises